Pemetaan pengetahuan terhadap perkembangan penelitian kebutuhan informasi pada database Scopus menggunakan VOSViewer - Ananda, Yonna; Rizal, Edwin; Rohman, Asep Saeful (Faculty of Communication, Padjadjaran University, 2025)
Information need is a cognitive condition where individuals seek relevant information to support decision-making and fulfill specific needs. Understanding information needs is crucial for comprehending information-seeking and use behaviors, especially in the increasingly complex digital age. This study aims to map the development of publications related to information needs, identify research trends and relationships between scientific concepts, as well as author collaboration networks (co-authorship) and keywords. This mapping is beneficial for academics, policymakers, and information professionals. This quantitative descriptive study employed a bibliometric approach, analyzing 3,941 English-language documents indexed in Scopus from 2014 to 2024, using the keyword